Banking Consumer Arbitration as a Consumer Protection Authority on the Market of Banking Services - Piguła, Ewelina (Journal of Finance and Financial Law, 2016)
The issue of Consumer Protection is a key factor in the Development of Modern Economy. The market was under the influence of the Financial Services Consumer Protection, because a significant role is also played by their behavior. It is very important, but customer safety and the effects of their decisions. To provide consumers with effective and efficient protection is very important to the functioning of the apartment next to the structures of the judicial system structures arbitration upholders of the law and the interests of consumers, which are the guarantees of fair and sound principles Economic Trade in the area of Banking Services. Among the institutions that can play a very large role in this scope, which are characteristic only for the Banking Sector, indicate Banking Ombudsman and created in 2008 Court of Arbitration by the KNF. The legislation provides for Multiple Sources of Consumer Protection of the interests of the banking services market, but not dating of these are known to consumers and used in practice. One of the often overlooked authorities Consumer Banking Services is Banking Ombudsman. The following article presents institution of Banking Ombudsman as an organ of big importance for consumer protection, allowing for extra-judicial resolution of disputes. The aim of the article is to present and evaluate the functioning of the Banking Ombudsman as an institution of Consumer Protection on the Market of Banking Services. This hypothesis requires proof that will be developed on the basis of its own research and source literature.